Contemplating the future: Acting now on long‐term monitoring to answer 2050's questions. (7th January 2015) - Lindenmayer, David B.; Burns, Emma L.; Tennant, Philip; Dickman, Chris R.; Green, Peter T.; Keith, David A.; Metcalfe, Daniel J.; Russell‐Smith, Jeremy; Wardle, Glenda M.; Williams, Dick; Bossard, Karl; deLacey, Claire; et al.
Abstract In 2050, which aspects of ecosystem change will we regret not having measured? Long‐term monitoring plays a crucial part in managing Australia's natural environment because time is a key factor underpinning changes in ecosystems. It is critical to start measuring key attributes of ecosystems – and the human and natural process affecting them – now, so that we can track the trajectory of change over time. This will facilitate informed choices about how to manage ecological changes (including interventions where they are required) and promote better understanding by 2050 of how particular ecosystems have been shaped over time. There will be considerable value in building on existing long‐term monitoring programmes because this can add significantly to the temporal depth of information. The economic and social processes driving change in ecosystems are not identical in all ecosystems, so much of what is monitored (and the means by which it is monitored) will most likely target specific ecosystems or groups of ecosystems. To best understand the effects of ecosystem‐specific threats and drivers, monitoring also will need to address the economic and social factors underpinning ecosystem‐specific change. Therefore, robust assessments of the state of Australia's environment will be best achieved by reporting on the ecological performance of a representative sample of ecosystems over time. Political, policy and financial support to implement appropriate ecosystem‐specific monitoring is a perennial problem. We suggest that the value of ecological monitoring will be demonstrable, when plot‐based monitoring data make a unique and crucial contribution to Australia's ability to produce environmental accounts, environmental reports (e.g. the State of the Environment, State of the Forests) and to fulfilling reporting obligations under international agreements, such as the Convention on Biological Diversity. This paper suggests what must be done to meet Australia's ecological information needs by 2050.